Guiding Lineage Specific Differentiation of SHED for Target Tissue/Organ Regeneration - Han, Yuanyuan; Zhang, Lili; Zhang, Chengfei; Dissanayaka, Waruna L. (Current Stem Cell Research & Therapy, 2021)
Stem cells from Human Exfoliated Deciduous teeth (SHED) are considered one of the most attractive cell sources for tissue engineering due to their easy acquisition with no donor morbidity, ready availability, ability to self-renew with high proliferation, capacity for multilineage differentiation and immunomodulatory functions. To date, SHED are able to differentiate into odonto-/ osteoblasts, neuronal cells, endothelial cells, hepatocyte-like cells, chondrocytes, epidermal cells among many other cell types. Accordingly, SHED possess a promising potential to be used in the cell-based therapy for various diseases, including reversible pulpitis, orofacial bone defects, neurodevelopmental disease and ischemic injury. Despite this potential, it has been a concern that tissue specific stem cells do not differentiate with the same efficacy into all the different lineages as they may have an inherent tendency to differentiate toward the tissues from which they were originally derived. Furthermore, stem cell niche comprises of a complex microenvironment where various cells, soluble signals, extracellular matrix and physical cues interplay to maintain the stemness of SHED and modulate their differentiation. Therefore, it is of significant importance to identify the specific microenvironmental cues that regulate lineage specific differentiation of SHED, which could inspire to develop functional approaches in target tissue regeneration. In this review, we highlight the recent studies that demonstrated multilineage differentiation capacity of SHED, focusing on how the microenvironment could be modified using different cues in order to achieve tissue specific regeneration.
Keywords: tissue engineering